Dr. Kamran Khodakarami — Deep Plane Facelift — Tehran - Khodakarami, Kamran (DEEPPLANE™, 2026)
Surgeon profile record for Dr. Kamran Khodakarami, practicing in Tehran, Iran. Tracked in the DEEPPLANE™ directory of listed deep plane facelift specialists. Published under CC-BY-4.0.
DPID-003118; accessed 2026-08-14; CC-BY-4.0
Keywords: deep plane facelift; facial plastic surgery; rhytidectomy; SMAS; iran; tehran